Proceedings of the First International Conference on Social Science, Humanity, and Public Health (ICOSHIP 2020) 2021
DOI: 10.2991/assehr.k.210101.025
|View full text |Cite
|
Sign up to set email alerts
|

Modisco With Moringa Leaf for Improving Childhood’s Nutritional Status

Abstract: Child growth is recognized as an important indicator of nutritional and health status. But in fact, there are still some cases of undernutrition in some areas of Jember. This is certainly a challenge for health providers because the lack of nutrients that occur in this golden period is irreversible. This research aims to analyze the effects of modisco with moringa leaf for improving the childhood's nutritional status. It was a quantitative research and conducted by using quasiexperimental study. This research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…In Nurina's (2020) study, giving soybean Modisco to KEP white rats for 14 days was able to increase body weight by an average of 55.33 grams (54.9%) (12).Muflihatin's research (2021) stated that children who were given Modisco with Moringa leaves for 7 days, had 56.6 times greater potential to increase their weight than those who were not given. So it can be concluded that the consumption of f Modisco with Moringa leaves has a beneficial effect on improving the nutritional status of children(6). in Arolyumma's research (2016) concluded that there was a significant difference in body weight change before and after giving Modisco ice cream(13).…”
mentioning
confidence: 99%
“…In Nurina's (2020) study, giving soybean Modisco to KEP white rats for 14 days was able to increase body weight by an average of 55.33 grams (54.9%) (12).Muflihatin's research (2021) stated that children who were given Modisco with Moringa leaves for 7 days, had 56.6 times greater potential to increase their weight than those who were not given. So it can be concluded that the consumption of f Modisco with Moringa leaves has a beneficial effect on improving the nutritional status of children(6). in Arolyumma's research (2016) concluded that there was a significant difference in body weight change before and after giving Modisco ice cream(13).…”
mentioning
confidence: 99%